A Review on Monkey Pox: Role of One Health Approach Against Monkey Pox - Aliyi Husein Sead; Aliye Hussein Johar; Geinoro Alleyo Tariku; Abdo Jilo Sufian (Journal of Public Health International, 2023)
The Ortho-poxvirus virus, which causes monkey pox, is a member of the Poxviridae genus. It was initially found in primates. In 1970, the Democratic Republic of the Congo reported the first instance of monkey pox. From there, it spread to a number of countries both inside and outside of Africa. There are two genetic varieties of monkey pox, which have been spread to people through respiratory droplets, and touch with objects contaminated by an affected person and consequently is often encountered in work situations. Among the countries with the worst effects are Nigeria and the Democratic Republic of the Congo. Non-human primates, rats, squirrel, and or mice are just a few of the creatures that can become infected by monkey pox. Although the origins of monkey pox infections are unknown, rodents from Africa and non-human primates like monkeys may contain the viruses and infect humans. Monkey pox is more likely to naturally infect rodents. Monkey pox has symptoms and lesions that are difficult to distinguish from smallpox in its clinical manifestations. Fever, chills, migraines, tiredness, tonia, swollen lymph nodes, back pain, and myalgia are some of the clinical symptoms of monkey-pox. A few examples of diagnostic tests include immune-fluorescent antibody assays, enzyme-linked immune-sorbent assays, and real-time polymerase chain reactions. A specialized vaccine that offers complete protection against by them on key-pox virus exists, yet there is no specific therapy for human monkey infection and interaction with the vaccinia virus. Smallpox vaccination can give cross-immunity with partial protection against infection and a reduction in symptom severity. Unfortunately, community health effects in the view of one health approach has not been addressed in vast. Therefore, the objectives of this review paper are to discuss the community health effects of monkey pox and to emphasize the role of one health approach against monkey pox.
Keywords: Human